Optimalisasi Pengembangan Karier, Keseimbangan Kehidupan Kerja, dan Manajemen Stres untuk Meningkatkan Kinerja Karyawan pada UMKM Pengrajin Kulit - Yudi Wahyudin Suwandi; Asep Ghofir Ali; Imas Komariyah (Society, 2025)
This research comprehensively analyzes the impact of career development, work-life balance, and stress management on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in the leather craft sector. The MSME sector plays a strategic role in the national economy, particularly in job creation and its contribution to GDP. However, employees in this sector often face challenges such as production pressures, limited opportunities for professional development, and high workloads, all of which can affect performance. The quality of human resources, including limited skills, is also a persistent issue among leather artisans. This study employs a quantitative approach by distributing questionnaires to 186 employees of leather-related MSMEs. The results indicate that career development, work-life balance, and stress management have significant impacts, both individually and simultaneously, on improving employee performance. Based on these findings, the research proposes implementation strategies such as skills training programs, flexible work policies, and work-environment-based stress management initiatives. Training provided by relevant agencies, including management and technical skills development, along with the provision of supporting equipment and facilities, is expected to improve production outcomes and product quality. This research offers both theoretical and practical contributions and serves as a valuable reference for MSME owners in managing human resources more effectively and sustainably.